Leadership qualities of university librarians in Malaysia / Kamariah Nor Mohd Desa - Mohd Desa, Kamariah Nor (2015)
The purpose of this study is to explore the leadership qualities required for Malaysian public university librarians that enhances customer satisfaction. The objectives of the study are (1) to examine the perceptions of librarians on their leadership qualities, (2) to examine the perceptions of subordinates on the leadership qualities of their librarians, (3) to examine the perceptions of the heads of departments on the leadership qualities of librarians who are their subordinates, (4) to assess the satisfaction of customers on library services, (5) to examine the relationship between the various dimensions of leadership qualities, (6) to compare the perceptions of different groups of respondents on leadership qualities, (7) to compare the perceptions of users on the imp0l1ance and performance of library services, and (8) to identify factors (e.g. transformational leadership, emotional intelligence and servant leadership) affecting leadership skills. The study covers 20 public university libraries in Malaysia. Respondents are librarians at all levels, head of departments, subordinates and library customers. The survey method is adopted. Data are collected through four (4) sets of questionnaires. The study adopts the 360 degree method in which the perceptions of respondents are gauged from multiple perspectives, thereby providing more data and information. Descriptive statistics of perception scores such as demographic profiles, means and standard deviations for each dimension are tabulated. Analytical methods for inferential statistics such as correlation analysis, statistical tests of significant differences, gap analysis and regression analysis are conducted. The results show that librarians are very positive about their leadership qualities, however they are moderately capable of understanding abstract ideas. Supporting staff rate the leadership qualities of their librarians lower than the librarians themselves and claim that the librarians are less likely to admit their mistakes or make sacrifices for others. Head of departments are more positive on the leadership qualities of their librarians particularly with respect to commitment and preserving organisation integrity. However they acknowledge and correspond to the librarians' perceptions that librarians are moderately capable to understand abstract ideas. There are differences in the perceptions of different groups of respondents on leadership qualities. Library customers are generally satisfied with most of the services offered but need to improve wireless access, computer facilities, online resources for their users and user friendly websites. However, the overall gap analysis of library services show the results of importance and performance mean scores (m=0.398) and are significantly different (p<0.01). There are significant gaps between the expectation of customers and their satisfaction. The results also show irregularity of positive or significant impact on identifying factors (e.g. transformational leadership, emotional intelligence and servant leadership) affecting leadership skills. This study is significant as it contributes to the body of knowledge in leadership qualities of university librarians. It contributes to new knowledge concept, instruments and 360 degree approach. It benefits public university libraries, faculties, researchers and the Ministry of Education (MOE) and nation.